2018
DOI: 10.1016/j.dsr2.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

A statistical approach to relationships between fluid emissions and faults: The Sea of Marmara case

Abstract: The Sea of Marmara is traversed by the North Anatolian Fault system and also presents abundant emission sites of methane gas into the water column. In order to assess the spatial relationship between gas emissions and active faults, the distribution of distances between gas emission sites and the nearest fault is calculated and compared with the distribution of distances between a uniform random distribution of points (Poisson process representing the null hypothesis of an absence of relationship between gas e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 91 publications
1
13
0
Order By: Relevance
“…With the possibility of distributed strike-slip across a few kilometre-wide zone of faults at the seafloor 26,30,42,43 , we might not have captured the complete possible slip. However, deformation is clearly focussed beneath the geodetic network since the fault trace can be unambiguously identified in the bathymetry 26,30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the possibility of distributed strike-slip across a few kilometre-wide zone of faults at the seafloor 26,30,42,43 , we might not have captured the complete possible slip. However, deformation is clearly focussed beneath the geodetic network since the fault trace can be unambiguously identified in the bathymetry 26,30 .…”
Section: Resultsmentioning
confidence: 99%
“…The offset can be explained with the increased strain and hence stress accumulation in the vicinity of the locked fault 37 (Fig. 5c) and gas migrations at depth 42,44 . The local observation is in-line with the sparse seismicity recorded by onshore stations during the last decade along this segment of the NAF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They form systems that can be viewed as flower structures and are possibly connected to a narrower damage zone at depth (Géli et al, 2018;Henry et al, this issue). The width of the shear zone at the surface, in this latter case, will depend of the depth in which the subsidiary shear planes splay from the main fault zone and on their dip.…”
Section: Evidence Of Permeability Enhancing At Fault Zonesmentioning
confidence: 99%
“…The presence of metastable ferromagnetic iron sulfide minerals on the Western High indicates a more reducing environment resulting from the degradation of heavy hydrocarbons and organic matter. The last article (Henry et al, 2018) links fluid emission and fault activity. It has been shown that most of the gas emissions are located within a distance shorter than 750 m from the faults, and irrespective of creeping or locked segments.…”
Section: Introductionmentioning
confidence: 99%